Potentially modifiable risk factors among veterans with spinal cord injury hospitalized for severe pressure ulcers: a descriptive study - Guihan, Marylou (Maney Publishing, 2012)
CONTEXT/OBJECTIVE: Pressure ulcers (PrUs) are a serious, costly and potentially life-long complication of spinal cord injury (SCI). Co-morbid conditions increase PrU risk, adding to the health behavior challenges faced by people with SCI. Little is known about medical co-morbidities, health beliefs, risk, protective behaviors, and readiness to improve skin care behaviors in people with SCI. This study describes the potentially modifiable medical and behavioral risk factors among veterans with SCI and severe (Stage III/IV) PrUs. DESIGN: Cross-sectional observational design. SETTING: 6 VA SCI Centers. PARTICIPANTS: Convenience sample from a larger intervention study of 148 veterans hospitalized for PrUs. INTERVENTIONS: Not applicable. OUTCOME MEASURES: Knowledge, PrU risk, skin protective behaviors, health beliefs, and practices, health locus of control, skin worsening. RESULTS: Most ulcers were stage IV (73%) and about half had 2+ PrUs. Participants reported a mean of 6.7 co-morbid conditions (respiratory, gastrointestinal, renal disease/urinary tract infection, autonomic dysreflexia, diabetes, bowel/bladder incontinence). Potential intervention opportunities include proactive assistance with management of multiple chronic conditions, substance abuse, nutrition, adherence to skin protective behaviors, readiness to change, and access to resources. Overall knowledge about PrUs was low, especially for how to prevent PrUs and what to do if skin breakdown occurs. CONCLUSION: Future research should address whether comprehensive models that include patient self-management, decision support and health care system, and proactive behavior change assistance for patients help reduce PrU incidence and recurrence in persons with SCI. TRIAL REGISTRATION: http://clinicaltrials.gov/ct2/show/NCT00105859